A8.07 Characterising effects of epigenetic regulation in assays using peripheral blood mononuclear cells from patients with inflammatory diseases. (24th February 2016) - Aftab, O; Sundström, Y; Bergqvist, F; Kultima, K; Gustafsson, MG; Larsson, R; Sundström, M; Ossipova, E; Lengqvist, J; Jakobsson, PJ; Rubin, J; Berg, L
Abstract : Background and objectives: Systemic inflammatory diseases, such as systemic lupus erythematosus (SLE) and myositis, have largely unknown aetiology and represent a disease area with majorunmet medical needs. Treatment often give a clinical effect, but not in all patients; and symptoms often remain. In collaboration with the Structural Genomics Consortium (SGC), we investigate cellular effects of chemical probes, which are drug-like molecules that can enter cells and which selectively inhibit potential new drug targets at therapeutically relevant doses. The effects we investigate are of two types, 1) either effects on expression of molecules which have been shown to be of pathological relevance in systemic inflammatory diseases, or 2) novel effects using unbiased analysis of the proteome. We have investigated cellular effects of 39 different probes which bind and inhibit epigenetic enzymes and regulators, such as bromodomains and histone methyltransferases. Material and methods: Peripheral blood mononuclear cells (PBMC) from healthy donors were incubated in presence of titrated doses (typically 0, 01 – 10uM) of 39 different chemical probes for 1, 3 and 6 days. Cell viability was determined using the Fluorometricmicroculture cytotoxicity assay which is based on measurements of FDA hydrolysis, or by flow cytometry using the live/dead marker viability IR® combined with markers for T cells, B cells and monocytes. Results: The viability of PBMC was affected by some of the epigenetic inhibitors and if so, viability decreased after 1–3 days of incubation. The two methods gave comparable results. In cases where the probes caused an increased cell death, it was typically seen in T cells, monocytes as well as in B cells. Planned studies: We aim to investigate disease relevant effects of these epigenetic chemical probes using PBMC from patients with SLE or myositis, in particular type I interferon responsiveness and B cell maturation in vitro . In addition, proteomic analysis of cells cultured in presence of these probes will be investigated in an effort to describe novel effects of inhibiting specific epigenetic regulators.